The Influence of Chinese College Students’ Physical Exercise on Life Satisfaction: The Chain Mediation Effect of Core Self-evaluation and Positive Emotion - Liu, Feiyang; Zhu, Zhengguang; Jiang, Bo (Frontiers in Psychology, 2021)
Physical exercise is an important way for college students to maintain their physical health, and life satisfaction is one of the important indicators of college students’ mental health. Therefore, this study aims to explore the relationship between physical exercise and life satisfaction of college students. Additionally, we also seek to demonstrate the chain mediating effects of core self-evaluation and positive emotion on this relationship. A total of 794 Chinese college students, 324 men and 470 women, participated in the study. The participants were 17–25years old (M=19.96±1.54). They completed the Exercise Adherence Questionnaire, Core Self-evaluation Scale, Positive Affect and Negative Affect Scale, and Satisfaction with Life Scale. Results showed a strong positive relationship between physical exercise and life satisfaction and verified the mediating effect of core self-evaluation and positive emotion on this relationship. The results also confirmed the chain mediating model between physical exercise, core self-evaluation, positive emotion, and life satisfaction. It enlightens us that we should pay more attention to the organic combination of students’ physical activities and mental health education.